Media e-komik strip “gege & gizi” terhadap pengetahuan dan sikap remaja tentang gizi seimbang - Diastuti, Putri Permata; Hardini, Deisy Sri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Improper implementation of balanced nutrition is a major problem that occurs among adolescents. Nutritional problems in adolescents can arise due to incorrect attitudes or eating patterns. Inadequate nutritional fulfillment with nutritional intake below the recommended normal. While excessive nutrition is caused by nutrition that exceeds normal. Purpose: To determine the effect of the comic strip